Dividends or share repurchases? Investigation of factors affecting the decisions: Empirical study on FTSE 350 companies - Tran, Uyen (2011)
Payout policy has remained as one of the most pertinent aspects for firms. When it comes to the decision of paying stockholders, firms have to take into account many different factors. Since cash dividend has been the dominant form of payout, the emergence of share repurchase as another form of payout has raised many questions. This paper examines the common determinants of dividend and share repurchase decisions for the components of FTSE 350 Index, consisting of the 350 largest companies by market capitalization listed on the London Stock Exchange, over a twenty-year period, from 1991 to 2010. Out of all the variables chosen as factors affecting the decisions of dividend and share repurchase, which are firm size, profitability, investment opportunity, tax, debt-to-equity ratio, and retained earnings, the three main factors showing the strongest effect are firm size, profitability, and investment opportunity. This is in line with Fama and French’s research (2001), and other literature. Although dividend per share has some certain influence on share repurchase, the relationship is positive, quite contrary to expectation. The decision of dividend payout is also affected by the amount of tax paid and retained earnings; whereas, share repurchase decision seems to be irrelevant to those factors.